Investigation of Mir-34b/c Gene Methylation in Patients with Papillary Thyroid Disease Compared to Healthy Individuals - Hoseini, Hosnie (International Journal of Pharmaceutical & Biological Archive, 2024)
Background and Objective: Papillary thyroid carcinoma (PTC) is the most frequent type of differentiated thyroid cancer. Recent advances have shown that cancer cells can have some epigenetic changes involved in all stages of cancer. It has also been shown that Mir-34b/c acts as a gene expression regulator in many biological processes, including angiogenesis. In the current study, to identify the potential role of Mir-34b/c in PTC progression, the methylation status of the Mir-34b/c promoter region has been evaluated. Methods: In this case-control study, blood samples were taken from 60 patients with papillary thyroid and 60 healthy people. The method of polymerase chain reaction method was used to investigate gene promoter methylation. The results obtained from the study were studied using Statistical Package for the Social Sciences and Chi-square tests respectively. Results: Findings confirm that there was a significant association between Mir-34b/c and gene promoter methylation. Conclusion: The results of the study showed that the reduction of gene promoter methylation in papillary thyroid cancer can be used as a biomarker in the diagnosis of the disease.